The Child attends a rural school: discussing child education legislation in rural areas - Marciane Maria Mendes; Rodrigo dos Santos; Marli Alves Batista Makowski (Revista Brasileira de Educação do Campo)
The object of this research is Early Childhood Education in and from the countryside. We analyzed the conditions of access to early childhood education for rural children in accordance with Brazilian legislation. We used qualitative research with a theoretical basis based on bibliographical research with authors who deal with the subject, as well as the official legislation that supports the subject in question. Initially, we highlighted early childhood education in rural areas as a right for children. The aim of the study is based on understanding the legal changes and how these directly affect children's lives at school (inside and outside). We found that with the changes in educational legislation for children under the age of four, there was a need for investment by the same regulatory body to meet the particular needs of the target audience, focusing mainly on those living in the most remote areas in the interior of the country. In this sense, we understand Early Childhood Education as a right for all children. Finally, we analyze the legal means by which government actions are developed with the prerogative of safeguarding educational rights, as well as promoting improvements in the field.